Pengembangan Gim Edukasi Pembelajaran Kata Benda dan Kata Kerja Bahasa Inggris pada Tingkat Sekolah Dasar - Ervian, Jenrico; Dirgantara, Harya Bima (KALBISCIENTIA Jurnal Sains dan Teknologi, 2024)
The purpose of this research is to develop an educational game that help elementary school children learn English vocabulary. The materials applied to the game are limited to nouns and verbs with matching card game types. The method used is Game Development Life Cycle (GDLC) with five stages: initiation, pre-production, production, game testing, beta testing, and release. The programming languages used are HTML, CSS, and Javascript. The final result of this research is an educational game "Pintar Kosakata" that can be played on the website. The results of black box testing state that all components run well. From the results of device testing, stated that the minimum width of the required device screen dimensions is 320 pixels. Based on the results of user experience testing, 7 out of 10 respondents stated that they understood the material of English nouns and verbs through the "Pintar Kosakata" educational game learning method.